Monitoring and Signaling of the Most Important Aphid Species in the Territory of Greater Poland and Silesia Provinces - Kamila Roik; Anna Tratwal; Sandra Małas; Jan Bocianowski (Agriculture)
Aphids are significant pests affecting crop yields both through direct feeding and as vectors of viruses. The monitoring focused on 10 of the most important aphid species. This study investigates the dynamics of aphid populations in two Polish regions, Winna Góra (Greater Poland Province) and Sośnicowice (Silesia Province), over a five-year period (2019–2023) using Johnson suction traps. Data collection covered species composition, migration timing, and seasonal variations in aphid abundance. Dominance patterns were assessed using a species-specific index, and inter-regional comparisons were analyzed through correlation and principal component analysis. Results indicate notable population peaks during autumn, suggesting this period is optimal for implementing control measures. The Johnson traps proved valuable for timely pest monitoring, offering predictive potential for future aphid migration, particularly in relation to virus-transmitting species critical to plants.